Erwerbungen 1990 - 2000 : Kunsthalle zu Kiel der Christian-Albrechts-Universität Schleswig Holsteinischer Kunstverein. - Beyer-Beckmann, Ute; Bergmann, Hans-Georg; Ermacora, Beate; Haensel, Ruprecht; Kersig, Thomas; Kähler, Ingeborg; Meyer, Jürgen H.; Schmidt, Hans-Werner; Shah, Anita; Thurmann, Peter; Welsch, Maren; Kunsthalle zu Kiel; et al. (Kiel : Kunsthalle zu Kiel, 2000)
Saxesen, Friedrich Wilhelm Reisig ; Curlitt, Louis (Heinrich L. Theodor) ; Dahl, Johan Christian ; Buntzen, Heinrich Christian August ; Schiertz, Franz Wilhelm ; Schirmer, Johann Wilhelm ; Wrage, Hinrich ; Repin, Ilja Jefimowitsch ; Styka, Jan ; Corinth, Lovis ; Sinesubow, Nikolaj Wladimirowitsch ; Heckel, Erich ; Aereboe, Albert ; Brockmann, Gottfried ; Radziwill, Franz ; Rickers, Hans ; Sigkou, O. ; Jawlensky, Alexej von ; Meistermann, Georg ; Hofer, Karl ; Mahlmann, Max H. ; Jorn, Asger ; Köpcke, Arthur ; Mortensen, Richard ; Hödicke, Karl Horst ; Nagel, Peter ; Lausen, Uwe ; Voss, Jan ; Koblasa, Jan ; Mulder, Jan ; Vana, Franz ; Ruthenbeck, Reiner ; Beuys, Joseph ; Jesdinsky, Bertram ; Kubota, Shigeko ; Duwe, Harald ; Scheibl, Hubert ; Roth, Uwe ; Witlatschil, Michael ; C., Sery ; Kluge, Gustav ; Porzner, Hans-Peter ; Wörsel, Troels ; Gutbub, Edgar ; Lechner, Alf ; Badur, Frank ; Oertel, Eberhard ; Lucebert ; Dahn, Walter ; Karp, Thomas ; Brus, Johannes ; Kumrow, Klaus ; Gerdes, Ludger ; Kaufmann, Andreas M. ; Doose, Erwin ; Gertsch, Franz ; Erben, Ulrich ; Bevan, Tony ; Duchow, Achim ; Bornefeld, Julia ; Knoebel, Imi ; Haberland, Heinke ; Weinberger, Lois ; Sauer, Michel ; Rheinsberg, Raffael ; Paik, Nam June ; Katase, Kazuo ; IRWIN ; Dwurnik, Edward ; Dumas, Marlene ; Rose, Rolf ; Pöggeler, Christoph ; Johnson, Tim ; Orlan ; Deckert, Christian ; Gaida, Klaus G. ; Andresen, Ulrike ; Doig, Peter ; Assig, Martin ; Gormley, Antony ; Meister, Ulrich ; Anger, Renate ; Regensburger, Tobias ; Honert, Martin ; Schütte, Thomas ; Jenssen, Olav Christopher ; Richter, Daniel ; Schwichtenberg, Bernhard ; Hansen, Britta ; Kollath, Ilka ; Plensa, Jaume ; Wassermann, Gudrun ; Arlt, Elsbeth
Duits
boek